A novel critique on ‘The scientific miracle of Qur’an philosophy’: an inter-civilization debate - Ahmad H.Osman, Rahmah; Ahmed Siddiqui, Naseeb (IIUM Press, International Islamic University Malaysia, 2018)
In recent decades we have been given one of the most interesting concepts in Islamic intellectual history, `the scientific miracle of Qur’an whereby the proponents have almost established the scientific theories in the Qur’an. However, such ardent claims must not come to be without any inspiration and methodology. This article, firstly, tries to trace the inspiration of such concept and then describe the methodology. However, as exciting as this concept seems, the methodology brings forth a very negative approach to prove the miracle of the Qur’an, which is value free. That negative value free mentality which is related to the status of prophet of Islam will be exposed and it will detail how the status of prophet of Islam was abated so badly to prove the science from the Qur’an. To counter this negative narrative and to reveal the true status of prophet of Islam, arguments will be presented from the Qur’an and Ḥadith which are incontrovertible. Let it be known than, this analysis is not general but particular. However, it will be a novel critique to re-visit this concept.